2020
DOI: 10.1021/jacs.9b13909
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Plasmonic Tungsten Oxide Quantum Wells with Controllable Free Carrier Densities

Abstract: We report the colloidal synthesis of ~3 tungsten-oxygen (W-O) layer thick (~1 nm), two-dimensional (2D) WO 3-x nanoplatelets (NPLs) (x ~ 0.55 Ð 1.03), which display tunable near-infrared localized surface plasmon resonances (LSPR) spectra and high free electron density (N e ) that arises predominantly from their large shape factor. Importantly, the W to O composition ratios inferred from their LSPR measurements show much higher percentage of oxygen vacancies than those determined by X-ray diffraction analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 46 publications
(101 reference statements)
4
56
0
1
Order By: Relevance
“…For instance, Prusty and coworkers prepared WO 3−x nanoplatelets through the oxidative decomposition of tungsten (V) ethoxide in the presence of myristic acid and oleylamine (OA). [33] They found that as the reaction temperature increased, the concentration of oxygen vacancies gradually increased, and the corresponding LSPR peak position also blue-shifted (Figure 2d). In addition, Liang and coworkers demonstrated that temperature played a vital role in introducing oxygen vacancies in WO 3−x nanosheets.…”
Section: Oxygen Vacancy Modulationmentioning
confidence: 96%
“…For instance, Prusty and coworkers prepared WO 3−x nanoplatelets through the oxidative decomposition of tungsten (V) ethoxide in the presence of myristic acid and oleylamine (OA). [33] They found that as the reaction temperature increased, the concentration of oxygen vacancies gradually increased, and the corresponding LSPR peak position also blue-shifted (Figure 2d). In addition, Liang and coworkers demonstrated that temperature played a vital role in introducing oxygen vacancies in WO 3−x nanosheets.…”
Section: Oxygen Vacancy Modulationmentioning
confidence: 96%
“…[1][2][3] In recent years, many efforts have been devoted to converting non-metals, in particular semiconductors, into metal-like plasmonic materials [4] by introducing dopants [5,6] or defects. [7][8][9] Owing to the merits of low cost, tunable electronic structure, high chemical activity, the plasmonic response has also been demonstrated by surfaceenhanced Raman spectra (SERS) of rhodamine 6G molecules adsorbed on H x MoO 3 , which exhibits an enhancement factor of 1.1 × 10 7 with a detection limit at a concentration as low as 1 × 10 −9 mol L −1 , representing the best among the hitherto reported metal oxides. Our findings have provided not only a set of promising new plasmonic materials, but also a general strategy to significantly increase the free-carrier concentration of non-metallic systems.…”
Section: Doi: 101002/adma202004059mentioning
confidence: 99%
“…Link等 [90] 在单粒子水平上观测到Au纳米棒的荧 光光谱, 发现单个Au纳米棒的荧光光谱类似于散射光 谱的形状, 并将其荧光归因于表面等离子体的辐射衰 变. Wackenhut等 [91] [82] . (b) 温度对WO 3−x 自由载流子密度的影 响 [83] . (c) LED照射下, Pd/MoO 3−x 表面H 2 产率的提高与波长的关系 [84] .…”
Section: 实现对单个纳米颗粒的光谱分析unclassified